Early warning processing results for June 15，2023 Qingpu，Shanghai M3.1 earthquake - Yongqian Shao; Chengrui Wang; Wei Wei; Peng Wang; Bo Bi (地震科学进展, 2024)
A M3.1 earthquake occurred in Qingpu District of Shanghai at 1:39 on June 15，2023. The Shanghai Earthquake Early Warning Network successfully received the earthquake early warning information released by the China Earthquake Early Warning Network，and the locally deployed Fujian Early Warning System EEW also successfully processed and produced the earthquake early warning results. In this paper，the results of 7 earthquake early warnings produced by Shanghai Earthquake Early Warning System and the earthquake early warning information released by China Earthquake Early Warning Network are compared and analyzed. The epicenter of the earthquake is located in the Shanghai Earthquake Early Warning Network. The first early warning information was released at 6.8 s after the earthquake. All 7 early warning processing results were produced within 15 s after the earthquake. Compared with the official earthquake catalogue，the first early warning processing result has an epicentral position deviation of 5 km and a magnitude deviation of −0.1. With the increase of the number of early warning stations involved in the calculation，the epicenter position is finally consistent with the official catalogue，and the magnitude deviation is also maintained at 0.5. The results of this earthquake early warning show that although Shanghai and its surrounding areas belong to the general early warning area with small and micro earthquakes as the main seismic activities，due to the large density of early warning stations，more accurate early warning processing results can also be produced in a short time after the earthquake，which is of great reference significance for the ongoing integration of monitoring and early warning business in the Yangtze River Delta.